2021
DOI: 10.1177/20458940211008069
|View full text |Cite
|
Sign up to set email alerts
|

Time trends of pulmonary endarterectomy in patients with chronic thromboembolic pulmonary hypertension

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is considered as a rare but severe complication after acute pulmonary embolism (PE) and is potentially curable by pulmonary endarterectomy (PEA). We aimed to evaluate, over an 11-year period, time trends of in-hospital outcomes of PEA in CTEPH patients and to investigate predictors of the in-hospital course. We analyzed data on the characteristics, comorbidities, treatments and in-hospital outcomes for all CTEPH patients treated with PEA in the German natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Mediastinitis and deep sternal wound infection rates, associated with deep hypothermic arrest in other forms of cardiac surgery, were reported in up to 6% of patients in international registries, but were not reported in series from individual centers (16). Whilst it is a positive step that three significant national registries published results in 2021, only one of these published morbidity data and pre-and post-operative haemodynamic outcomes (17,38,40). It will become increasingly important that these large-volume, well-supported prospective registries continue to collect and report data for CTEPH and patients undergoing PTE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mediastinitis and deep sternal wound infection rates, associated with deep hypothermic arrest in other forms of cardiac surgery, were reported in up to 6% of patients in international registries, but were not reported in series from individual centers (16). Whilst it is a positive step that three significant national registries published results in 2021, only one of these published morbidity data and pre-and post-operative haemodynamic outcomes (17,38,40). It will become increasingly important that these large-volume, well-supported prospective registries continue to collect and report data for CTEPH and patients undergoing PTE.…”
Section: Discussionmentioning
confidence: 99%
“…It was required in 0% to 56.3% of patients (median 5.5%), with indications including right ventricular support, failure to wean from cardiopulmonary bypass and failure to oxygenate due to reperfusion pulmonary oedema (9,(32)(33)(34). In the two largest reporting series it was required in 5.1 and 5.5% of patients (9,38). Survival for patients requiring ECMO ranged from 25% to 57% (25,35,72).…”
Section: Major Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…The different patterns of CTEPH between both sexes could have influenced the received treatment, but many other factors could also be related. In recently published work by Hobohm et al [ 30 ], the number of PEA also increased in Germany during the last 11 years, and in-hospital death decreased in parallel, suggesting that patient selection and institutional experience could be important determinants of outcomes. Regarding BPA, a contemporary experience of a Japanese referral center during the 2011–2019 period also showed that many more women were treated only with pulmonary vasodilators (66.7 of the total number of patients treated exclusively with medical therapy were women), and a higher number of women were treated with BPA (84.4% of the number of patients who only received BPA) when compared with the proportion of patients treated with PEA (56.2% of them women) or with the combination of PEA and BPA (64.0% of them women) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary embolism (PE) is the third most common cardiovascular disease with an annual incidence of 39–115 per 100,000 person-years and is associated with serious short- and long-term complications including recurrence, chronic thromboembolic pulmonary hypertension (CTEPH) and death 1 , 2 . CTEPH is a rare disease, but is associated with high mortality rates and poor prognosis if left untreated 3 , 4 . In recent years, microRNAs (miRNAs) emerged as novel biomarkers and distinct patterns were found to exhibit diagnostic and prognostic value for different disease settings, including various cardiovascular diseases 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%